Case report: Patient-derived organoids promoting personalized treatment in invasive urothelial carcinoma - Liu, Xun; Han, Xuebing (Frontiers in Oncology, 2024)
Tumor organoids, an in-vitro three-dimensional model, possess high potential for investigating tumor biology and treatment response and have been demonstrated more appropriate for drug assessment than two-dimensional cultures. Herein, we described two cases of invasive high-grade urothelial carcinoma who underwent radical cystectomy successfully following use of patient-derived organoids (PDOs) for drug screening to inform therapeutic decisions. In these two cases, the PDOs cultured by biopsy tissues were both sensitive to the combination of gemcitabine and cisplatin. After neoadjuvant chemotherapy (NAC) with gemcitabine and cisplatin, the patients responded well, and radical cystectomy was performed successfully. No recurrence or metastasis was observed within 6 months after surgery. This small case series suggests that the patient-derived urothelial carcinoma organoids contribute to optimizing NAC options to guide personalized treatment and improve the survival outcomes.